Sejarah dan Perkembangan Institusi Fatwa di Negeri Kelantan - Abd. Rahman, Noor Naemah (Jurnal Usuluddin, 2004)
The fatwa institution can be regarded as an important means for the dissemination of Islamic law to the society. In Kelantan, the fatwa institution had been long established and has undergone significant development. The institution represented religious authorities due to its close association with the Malay Sultan. Based on such scenario, this article tries to outline the historical development of the institution in Kelantan as well analysing its achievements pertaining to the legal aspect in Kelantan.